Social networks and dissatisfaction with body image among healthcare students - Santos, Bianca Soares dos; Fernandes, Nathália Dalla Vecchia; Masquio, Deborah Cristina Landi (O Mundo da Saúde, 2023)
Dissatisfaction with body image is an essential factor related to eating disorders. It is noted that social networks continually publicize the lean and muscular body types, which have contributed to the internalization of the ideal body. However, social networks’ influence on body image dissatisfaction in health university students must be clarified. This study aimed to investigate the relationship between dissatisfaction with body image and the use of social networks among undergraduate healthcare students. A cross-sectional survey was conducted, with online data collection using the Google Forms® platform. The sample consisted of 203 healthcare course students aged between 18 and 40 years. The Body Shape Questionnaire (BSQ) was applied to assess body image dissatisfaction. The influence of social networks on lifestyle was investigated by the score generated by the sum of six questions, with answers on a Likert scale. Socioeconomic information and selfreported weight and height were collected. Statistical analysis was performed using the JAMOVI software, considering a significance level of p≤0.05. The body image dissatisfaction score was significantly higher in women, and 65.4% had some degree of dissatisfaction. BMI, number of social networks accessed, and the overall media influence score were positively associated with dissatisfaction with body image. It is concluded that dissatisfaction with body image was associated with BMI, number of social networks, and social network influence score and was observed mainly in women.